Juridical Analysis of the Problems of Submitting Evidence in Land Dispute Resolution - Vebyangga, Ardilla Ayu; Isnaeni, Diyan; Muhibbin, Moh. (Academia Open, 2026)
General Background Land disputes remain complex civil law issues because land has economic value, social function, and strong links to ownership certainty. Specific Background In Decision Number 21/Pdt.G/2023/PN Png, the dispute involved competing claims between land pawning and land sale, both supported by privately executed documents. Knowledge Gap Previous land dispute studies have focused mainly on ownership rights, agrarian conflict, or certificate strength, while specific analysis of private written evidence in court decisions remains limited. Aims This study analyzes the problems of submitting evidence in land dispute resolution, particularly the probative value of private documents, legal capacity of the parties, and judicial consideration. Results Using normative juridical research with statutory, conceptual, and case approaches, the findings show that problems arose from disputed private documents, alleged signature irregularities, questions about legal capacity, and weak land administration legality due to the absence of an authentic deed made before a Land Deed Making Officer. The judge considered not only documents but also witness consistency, chronology of land possession, and the legal relationship between the parties. Novelty This study emphasizes private document vulnerability as a central evidentiary issue in land dispute adjudication. Implications Legal certainty requires stronger documentation quality, clearer legal relationships, and judicial caution in assessing private documents. Highlights: Unauthenticated documents created weaker legal standing. Witness consistency shaped judicial consideration. PPAT deed absence reduced ownership certainty. Keywords: Evidence, Land Dispute, Civil Proof, Legal Certainty.